2017
DOI: 10.22492/ijpbs.3.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Work-Family Conflict in Nursing: An Integrative Review of Its Antecedents and Outcomes

Abstract: The aim of this paper is to provide an integrative review of the literature on work-family conflict (WFC) in nursing, assessing the antecedents and consequences of nurses' productivity, physical and psychological health, and well-being. We searched electronic databases, focusing on articles published in English and Italian during the period of 2005 to 2017. From the 1,180 studies found, we selected 28 papers for this integrative review. The findings, expressed as narrative synthesis, show that WFC is a stresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…One study in Iran revealed that as many as 93% of nurses reported that their level of work–family conflict was moderate to high (Zandian et al., 2020). Work–family conflict is an established stressor in nursing (Gonnelli & Raffagnino, 2017) that affects physical and mental health (Gonnelli & Raffagnino, 2017) and quality of life of nursing staff (Zandian et al., 2020), and may lead to burnout at work and a high staff turnover rate (Asiedu et al., 2018). A meta‐analysis including 106 studies supported this hypothesis that work–family conflict contributes substantially to high turnover rates among nurses (Nei et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One study in Iran revealed that as many as 93% of nurses reported that their level of work–family conflict was moderate to high (Zandian et al., 2020). Work–family conflict is an established stressor in nursing (Gonnelli & Raffagnino, 2017) that affects physical and mental health (Gonnelli & Raffagnino, 2017) and quality of life of nursing staff (Zandian et al., 2020), and may lead to burnout at work and a high staff turnover rate (Asiedu et al., 2018). A meta‐analysis including 106 studies supported this hypothesis that work–family conflict contributes substantially to high turnover rates among nurses (Nei et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, among reviewed researches we have not found any papers concerning emotional regulation or emotional intelligence, which have been considered key factors for nursing health and well-being [12]. In addition, the balance between work and private life has been mentioned to a certain extent, but no research has been carried out concerning the work-family conflict, which is important in nursing research [75].…”
Section: Discussionmentioning
confidence: 99%
“…The psychosocial hazard that is often experienced by mothers who work as nurses is an imbalance between work and family due to multiple roles. The results of a review by Gonnelli and Raffagnino in 2017 showed that work-family conflict is a stressor in nursing and is the most analyzed risk factor in the workplace (Gonnelli, 2017). Conflicts that occur in nursing staff are supported by the results of a study by Agustian in 2015 which showed that there were 83.6% of nursing staff having high intrapersonal conflicts, these conflicts could come from patients, families or coworkers.…”
Section: Introductionmentioning
confidence: 94%